2003
DOI: 10.1128/jvi.77.2.1441-1451.2003
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus K-bZIP Is a Coregulator of K-Rta: Physical Association and Promoter-Dependent Transcriptional Repression

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is a human gammaherpesvirus that has been implicated in the pathogenesis of Kaposi's sarcoma and B-cell neoplasms. The genomic organization of KSHV is similar to that of Epstein-Barr virus (EBV). EBV encodes two transcriptional factors, Rta and Zta, which functionally interact to transactivate EBV genes during replication and reactivation from latency. KSHV encodes a basic leucine zipper protein (K-bZIP), a homologue of EBV Zta, and K-Rta, the homologue of EBV Rta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
128
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(138 citation statements)
references
References 41 publications
9
128
1
Order By: Relevance
“…Previously, we showed that K-bZIP is a strong transcriptional repressor, which modulates the transcription of K-bZIP and ORF57 promoters mediated by K-Rta (20,29). Based on ChIP assays, K-bZIP is recruited to these two promoters and Ori-Lyt DNA during the early phase of KSHV lytic replication (19).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we showed that K-bZIP is a strong transcriptional repressor, which modulates the transcription of K-bZIP and ORF57 promoters mediated by K-Rta (20,29). Based on ChIP assays, K-bZIP is recruited to these two promoters and Ori-Lyt DNA during the early phase of KSHV lytic replication (19).…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids encoding the full-length K-bZIP and K-Rta genes were described previously (20). This cloning introduced a CpoI site and a Flag tag or T7 tag at the N terminus of each protein as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations